The horseman's word - McHargue, Georgess (Delacorte Press, 1981)
When Leigh goes to Scotland to help her aunt and uncle with the horses on their farm, she becomes involved with a local boy, the grandfather who blackmails him, and the tradition of the Horseman's Word.